2008
DOI: 10.1182/blood-2007-10-117283
|View full text |Cite
|
Sign up to set email alerts
|

Circulating neutrophils maintain physiological blood pressure by suppressing bacteria and IFNγ-dependent iNOS expression in the vasculature of healthy mice

Abstract: Whether leukocytes exert an influence on vascular function in vivo is not known. Here, genetic and pharmacologic approaches show that the absence of neutrophils leads to acute blood pressure dysregulation. Following neutrophil depletion, systolic blood pressure falls significantly over 3 days (88.0 ± 3.5 vs 104.0 ± 2.8 mm Hg, day 3 vs day 0, mean ± SEM, P < .001), and aortic rings from neutropenic mice do not constrict properly. The constriction defect is corrected using l-nitroarginine-methyl ester (L-NAME) o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
31
0
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(34 citation statements)
references
References 42 publications
1
31
0
2
Order By: Relevance
“…30 For example, infiltration of neutrophils is important to initially activate or fully stimulate monocytes/macrophages in the vessel wall but has no effect on arterial hypertension induced by angiotensin II. 6 T cells but not B cells have been reported to promote vascular dysfunction and hypertension in mice after angiotensin II infusion or DOCA-salt stress.…”
Section: Discussionmentioning
confidence: 99%
“…30 For example, infiltration of neutrophils is important to initially activate or fully stimulate monocytes/macrophages in the vessel wall but has no effect on arterial hypertension induced by angiotensin II. 6 T cells but not B cells have been reported to promote vascular dysfunction and hypertension in mice after angiotensin II infusion or DOCA-salt stress.…”
Section: Discussionmentioning
confidence: 99%
“…at a faster rate. Activated neutrophils may suppress nitric oxide synthesis (iNOS) expression 51 , which could profoundly deteriorate kidney function 52 .…”
Section: Discussionmentioning
confidence: 99%
“…40 Telemetric blood pressure recordings revealed that ablation of LysM ϩ cells not only improved vascular dysfunction but also nearly abolished the increase in systolic blood pressure in response to ATII, paralleled by a strikingly decreased rate of vascular fibrosis and medial hypertrophy ( Figure 6). However, not only monocytes/macrophages but also neutrophils might contribute to blood pressure regulation 41 and, via their myeloperoxidase activity, to blood pressure increase in response to ATII. 42 Additionally, LysM ϩ neutrophils play a role in the progression of early atherosclerotic lesions, as demonstrated in monocyte-depleted ApoE Ϫ/Ϫ LysM egfp/egfp mice.…”
Section: Discussionmentioning
confidence: 99%